PATHOLOGICAL CHANGES IN MICE TREATED WITH CYCLOPHOSPHAMIDE AND EXOGENOUS DNA - E. V. Dolgova; V. P. Nikolin; N. A. Popova; A. S. Proskurina; K. E. Orishchenko; E. A. Alyamkina; Ya. R. Efremov; S. I. Baiborodin; E. R. Chernykh; A. A. Ostanin; S. S. Bogachev; T. S. Gvozdeva; et al. (Вавиловский журнал генетики и селекции)
The synergic action of the cytostatic drug cyclophosphamide (CP) and fragmented exogenous DNA causes illness and death in mice (Dolgova et al., 2011–2013). The observed «delayed death» effect was most clearly pronounced when the DNA preparation was administered 18 to 30 hours after CP treatment. This time span is designated as «death window».It was found that injections of exogenous DNA result in sustained increase in bone marrow cell (BMC) apoptosis, which occurs throughout the time of DNA administration (18–30 hours). Exogenous DNA, both allogeneic and belonging to various taxa induces BMCs apoptosis. Plasmid DNA has the greatest effect on apoptosis induction.The analysis of reduction and restoration of BMC subpopulations as the mice progressed to death revealed a virtually complete loss of the 12–20-mkm fraction of the cell population (about 3–4 % vs. 35–40 % in the control), which corresponds to the maximum leukopenia on day 3 after CP treatment. However, the relative amount of CD34+ hematopoietic stem cells (HSCs) from day 15 and till the end of the observation constituted 1,2–1,4 %, which corresponds to the wild-type range. Comparison of BMC smears from the sternal bone marrow of the CP and CP+DNA groups of mice indicates that the BMC populations isolated from CP+DNA animals lack young committed lymphopoiesis progenitor cells. Moreover, the affected mice had immature blast cell types in their blood, which was never observed in healthy or CP-treated mice. Pathological and morphological analyses show that starting from posttreatment day 9, mice that received CP+DNA preparations displayed pronounced morphological changes in their lungs, liver, pancreas, central and peripheral immune system organs, and brain. Most of the pathological changes observed are consistent with severe inflammatory response. This suggestion is proven by structural equivalents of functional involution of lymphoid organs, such as thymus, spleen, and lymph nodes.We speculate that the death of treated animals resulted from multiple organ dysfunctions caused by accidental involution of lymphoid organs and the systemic inflammatory response syndrome, both associated with injections of fragmented exogenous DNA into experimental animals within the «death window», which corresponds to the final step in the repair of the majority of CP-induced double-strand breaks.